IL-4 down-regulates the surface expression of CD5 on B cells and inhibits spontaneous immunoglobulin and IgM-rheumatoid factor production in patients with rheumatoid arthritis. - Hidaka, T (1992)
There is evidence to suggest that CD5+ B cells may be associated with autoimmunity, e.g. they are increased in patients with rheumatoid arthritis (RA). In this study, we found that the expression of CD5 on RA B cells increased spontaneously, following culture for up to 4 days in vitro in the absence of T cells, supporting the idea that the CD5+ B cell possesses distinctive features. The spontaneous increase of CD5 expression was down-regulated by recombinant IL-4 (rIL-4). Other cytokines studied (rIL-1 alpha, rIL-2, rIL-5, rIL-6) did not alter CD5 expression. Studies of antibody production showed that rIL-4 could reduce spontaneous production of total IgG and IgM in non-stimulated RA T plus B cell cultures. Spontaneous production of IgM rheumatoid factor (IgM-RF), measured by a newly developed avidin-biotin complex ELISA, was also reduced by rIL-4. Furthermore, rIL-4 reduced the increase in IgM-RF production observed on stimulation with Staphylococcus aureus Cowan I (SAC) or pokeweed mitogen (PWM). Thus, IL-4 might act as a regulator of the development of abnormal B cell differentiation in patients with RA.